The The Mutation Effect of Neuraminidase and Screening Bioactive Compound to Inhibiting Neuraminidase in H5N1 - Ruslan, Syafrudin; Ernawati, Nina (Bioinformatics and Biomedical Research Journal, 2018)
Mutation that occur in the virus help to avoid the host's immune system and are passed on to the next generation and synthetic compounds begin to cause influenza viruses to be resistant. The purpose of this study was to determine the effect of mutations and inhibiting compounds for neuraminidase on the H5N1 virus. All DNA neuraminidase 1 (NA1) sequences from the H5N1 virus in 2016 were downloaded through NCBI and converted into protein sequences in ExPASy. Amino acids are aligned with Clustal Omega in EMBL-EBI and HOPE servers to predict mutation effects. Amino acid sequence A/chicken/Subang/08160018-002/2016 is used to represent neuraminidase in Indonesia. Protein molecular modeling is done using Swiss Model and Fugue, the results of subsequent modeling in Ramachandra. Eight natural compounds from plants and two control compounds, zanamivir and oseltamivir were used as ligands, docked using PyRx and visualized with PyMOL and LigPlot +. As many as 11 amino acid sequences used there are 30 regions in sequences that are mutated and alter the function of neuraminidase which initially as exo-alpha-sialidase activity becomes hydrolase activity. The docking results show that rosmarinic acid, rosmanol, chlogenic acid, oleonolic acid, carnosic acid, caryophyllene and capsaicin have binding affinity between zanamivir and oseltamivir. Visualization shows that rosmarinic acid, chlorogenic acid, rosmanol, and capsaicin compounds are predicted to replace zanamivir and oseltamivir. Because mutations in neuraminidase alter the function of neuraminidase from exo-alpha-sialidase activity into hydrolase activity and rosmarinic acid, chlorogenic acid, rosmanol, and capsaicin compounds are predicted to be inhibitors for NA1.